Testing of active air terminals for ACMV systems - Han, Nigel Fu Hong (2016)
Nowadays, active chilled beam is used in many indoor buildings worldwide due to its’ advantages such as cost saving and low energy consumption. Therefore, it is significant to evaluate the air distribution in an occupied space to ensure appropriate thermal comfort level. Although various studies have been carried out, the research on both air distribution and thermal comfort were still insufficient. This experiment was carried out in the thermal lab to determine the air distribution in the primary air plenum as well as in the thermal room. The air distribution in the thermal room was assessed by controlling a mobile robot to a set of fixed points with the main purpose of measuring the airflow velocity and temperature. The Air Diffusion Performance Index (ADPI) and Draft Rate (DR) was calculated using the two parameters measured and the results were discussed. An ADPI of 84.44% is achieved and it showed that the air distribution in the thermal room is considered to be satisfactory. Also, the overall DR in the thermal room was found out to be low. The air distribution in the primary air plenum was evaluated and it was discovered that the air flows asymmetrically from the nozzles. Future work can incorporate Computational Fluid Dynamics (CFD) simulation to better compare and contrast with the experimental results.